2011
DOI: 10.2337/db10-1805
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency for Costimulatory Receptor 4-1BB Protects Against Obesity-Induced Inflammation and Metabolic Disorders

Abstract: OBJECTIVEInflammation is an important factor in the development of insulin resistance, type 2 diabetes, and fatty liver disease. As a member of the tumor necrosis factor receptor superfamily (TNFRSF9) expressed on immune cells, 4-1BB/CD137 provides a bidirectional inflammatory signal through binding to its ligand 4-1BBL. Both 4-1BB and 4-1BBL have been shown to play an important role in the pathogenesis of various inflammatory diseases.RESEARCH DESIGN AND METHODSEight-week-old male 4-1BB–deficient and wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…Moreover, AT inflammation and hepatosteatosis were decreased, whereas glucose tolerance was improved (49). Counterintuitively, antibody-mediated stimulation of CD137 also reduced body weight, adiposity, and IR (67).…”
Section: Cd137-cd137lmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, AT inflammation and hepatosteatosis were decreased, whereas glucose tolerance was improved (49). Counterintuitively, antibody-mediated stimulation of CD137 also reduced body weight, adiposity, and IR (67).…”
Section: Cd137-cd137lmentioning
confidence: 88%
“…Hence, costimulatory interactions are likely to mediate a rather broad crosstalk between innate and adaptive immunity during the pathogenesis of obesity and its related complications. Multiple costimulatory dyads of the B7 family and the tumor necrosis factor superfamilies are expressed on cell types involved in obesity-associated inflammation, and some have been identified as critical contributors to the pathogenesis of obesity (Table 1) (32,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: T-cell Antigen-presenting Cell Interactions In Obesitymentioning
confidence: 99%
“…Indeed, we and others previously demonstrated a requirement for the costimulatory molecules CD40L and 4-1BB to maintain adipose tissue inflammation in mice. 16,23,24 Surprisingly, Guo et al 18 previously suggested a protective role for the CD40 receptor in adipose tissue inflammation. In their study, CD40 −/− mice exhibited a hyperinflammatory phenotype with increased immune cell accumulation, elevated cytokine levels, hepatic steatosis, insulin resistance, and glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, interaction between 4-1BB and 4-1BBL on endothelial cells and macrophages is involved in vascular inflammation [14, 15], and interaction between the two molecules on epithelial cells and natural killer cells is involved in renal ischemia-reperfusion injury [16]. We previously showed that expression of 4-1BB and 4-1BBL was upregulated in adipose tissue that was inflamed due to obesity, and that ablation of 4-1BB reduced adipose inflammation [17]. Hence, we hypothesized that interaction between 4-1BB and 4-1BBL on adipose cells and immune cells such as macrophages plays a role in adipose inflammation in obesity.…”
Section: Introductionmentioning
confidence: 99%